Machinability studies on Al7075-based hybrid composites reinforced with SiC, graphene and CNT. (12th January 2021) - Ajithkumar, J.P.; Xavior, M. Anthony
This experimental study analyses the machinability of two composites namely: 1) Al7075-10%SiC-0.1% grapheme; 2) Al7075-10%SiC-0.1% CNT by turning process using uncoated and diamond-like carbon (DLC) coated carbide inserts. Composites were fabricated through united stir and squeeze casting process with ultra-sonification. The effect of graphene and CNT on cutting force, surface roughness, flank wear, crater wear and chip morphology were quantified and presented. Graphene-based composite, recorded the highest cutting force (383.4 N) followed by CNT-based (318.6 N). Higher surface roughness (0.8519 μm) was observed in CNT-based composite and least in (0.4428 μm) graphene-based. CNT-based composite recorded the highest flank wear (0.3544 mm) and graphene-based observed the least flank wear (0.2253 mm). It was also noted that the presence of graphene showed more influence in the chip morphology. Further, the effect of graphene and CNT reinforcements on the micro-structural properties were also investigated.